Aun (n = 1–16) clusters on the ZrO2(111) surface: a DFT+U investigation. Issue 44 (26th October 2016) - Liang, Ming-Xing; Zhao, Liang; Jia, Jianfeng; Wu, Hai-Shun
Abstract : Au n ( n = 1–16) clusters supported on the monoclinic ZrO2 surface prefer quasi-planar geometries that lay flat on the surface. Abstract : The growth patterns and electronic structures of Au n clusters ( n = 1–16) supported on the monoclinic ZrO2 (111) surface were investigated using a DFT+ U approach. We found that the supported Au n clusters prefer quasi-planar structures and lay flat on the ZrO2 surface. This result agrees well with the experimental results. Both orbital overlap and dispersion interactions contribute to the interaction between the Au n cluster and the ZrO2 surface. Electrons were transferred from the ZrO2 surface to the Au n cluster. Small energy gaps between unoccupied states in the Au n clusters and occupied states in the ZrO2 surface were found, especially for the supported Au n clusters with odd n, which may indicate that more electrons are excited from the ZrO2 surface to the Au n cluster even under visible-light irradiation. In other words, the ZrO2 support may be involved in the photocatalytic process when Au n /ZrO2 is used as a photocatalyst.